Economic aspects of the logistics systems management in a small business - Shyshkin, Viktor; Onyshchenko, Oksana; Tur, Danylo (Management and Entrepreneurship: Trends of Development, 2022)
The article analyzes theoretical foundations of enterprises logistics system construction, gives the classification of main entrepreneurial activity subjects in Ukraine, traces key development trends and outlines a role of small business in the national economic system, conducts a comparative analysis of small and medium entrepreneurship specific weight and defines the main key economical aspects of managing their logistics system. The research conducted studies the theoretical foundations of the formation of ways to optimize the movement of goods in the logistics system of a small business entity with the aim of minimizing economic costs. It states that appropriate management decisions due to the optimization of the logistics system of small business entities should be made regarding delivery terms, taking into account costs and revenues, the feasibility of using outsourcing, the type of vehicle, the number of delivery points, their size and locations.JEL Classification: D21, L23